2003
DOI: 10.1074/jbc.m209385200
|View full text |Cite
|
Sign up to set email alerts
|

A New Phosphatidylinositol 4,5-Bisphosphate-binding Site Located in the C2 Domain of Protein Kinase Cα

Abstract: In view of the interest shown in phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P 2 ) as a second messenger, we studied the activation of protein kinase C␣ by this phosphoinositide. By using two double mutants from two different sites located in the C2 domain of protein kinase C␣, we have determined and characterized the PtdIns(4,5)P 2 -binding site in the protein, which was found to be important for its activation. Thus, there are two distinct sites in the C2 domain: the first, the lysinerich cluster locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 60 publications
(64 reference statements)
9
100
1
Order By: Relevance
“…In its Ca 2ϩ -bound state, this protein fold mediates an electrostatic interaction with acidic phospholipids, phosphatidylserine and phosphatidylinositol 4,5-bisphosphate (55,56), and translocates the kinase to the plasma membrane (47). In addition, Ca 2ϩ binding induces conformational changes in the regulatory domain of the kinase (47), thereby affecting its binding properties toward protein ligands (57).…”
Section: Discussionmentioning
confidence: 99%
“…In its Ca 2ϩ -bound state, this protein fold mediates an electrostatic interaction with acidic phospholipids, phosphatidylserine and phosphatidylinositol 4,5-bisphosphate (55,56), and translocates the kinase to the plasma membrane (47). In addition, Ca 2ϩ binding induces conformational changes in the regulatory domain of the kinase (47), thereby affecting its binding properties toward protein ligands (57).…”
Section: Discussionmentioning
confidence: 99%
“…Also of functional consequence is a cationic patch in the concave face of the bsandwich, termed the cationic b-groove, which varies in size and electrostatics among C2 domains (13). Cationic b-grooves have been shown to bind ceramide-1-phosphate (36) as well as PIs including PI(4,5)P 2 (37). Thus, many C2 domains are able to coordinate multiple lipids in both a Ca 21 -dependent or independent manner.…”
Section: C2 Domainsmentioning
confidence: 99%
“…Earlier studies have suggested that lysines 197 and 199 in the ␤3 strand and lysines 209 and 211 in the ␤4 strand of PKC␣C2 are important in Ca 2ϩ -independent, PIP 2 -dependent binding to vesicles, PSand PIP 2 -dependent regulation of PKC␣ activity in vitro, and membrane residence (Ochoa et al, 2002;Corbalan-Garcia et al, 2003;Rodriguez-Alfaro et al, 2004;Marin-Vicente et al, 2005). The hypothesis that these lysine residues are important in PIP 2 recognition predicts that mutations at these positions would weaken membrane-targeting specificity in vivo and lipid-binding affinity in vitro.…”
Section: Intracellular Targeting and Lipid Binding Of Mutant Pkc␣ C2 mentioning
confidence: 99%
“…Domain-containing the PKC␣ C2 Ca 2؉ -binding Loops and the ␤3-4 Hairpin A basic region formed by lysine residues in the ␤-hairpin formed by ␤ strands 3 and 4 has been postulated to coordinate PS or PIP 2 in the membrane (Ochoa et al, 2002;Corbalan-Garcia et al, 2003;Rodriguez-Alfaro et al, 2004;MarinVicente et al, 2005), and an electron paramagnetic resonance study has demonstrated that this ␤3-4 hairpin lies in close proximity to the membrane surface (Kohout et al, 2003). To investigate the contribution of the ␤3-4 hairpin to specific Figure 5.…”
Section: Intracellular Targeting and Lipid Binding Of A Hybrid C2mentioning
confidence: 99%
See 1 more Smart Citation